Metallurgy and Structure of Casting Alloy Cu-30Zn Cast in Sand Moulds - Machuta, Jiri; Nova, Iva; Horacek, Josef (Manufacturing Technology Journal, 2016)
Currently at our department - Department of Engineering Technology - Technical University in Liberec), we are under-tracking properties of copper alloys. This article is dedicated of the brass (Cu-30Zn), which is used for production of decorative castings. With production of decorative castings deal various foundries in the Czech Republic. The staff of these foundries for long periods gained a lot of experience in metallurgy and preparation of the copper alloy melts. In terms of our foundry there is little available literature data, which would characterize the crystallization and solidification of castings produced from single and multicomponent brass. Our department is involved in research of copper and its alloys. This article contains a description of crystallization of copper alloys (70%) - Cu-30Zn and proving phase analysis structure of the production of test casting shape of desk in the sand mould.
Keywords: brass; decorative castings; metallurgy alloys; crystallization; microstructure